Faktor yang Mempengaruhi Kepuasan Konsumen dan Minat Beli Ulang Pada Bisnis Bridal dan Make-Up - Aurel Jovandio Cahyadi; Dhyah Harjanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
People's lifestyles that are increasingly paying attention to appearance cause the bridal and make-up service business to be increasingly in demand. Bridal and make-up service businesses are now serving weddings and various events. This condition causes the bridal and make-up businesses must be more competitive. Service providers must be able to understand the factors that can satisfy consumers and make them willing to make repeat purchases. This study aims to test whether service quality, product quality, and price reasonableness can increase satisfaction and generate repurchase interest in bridal and make-up business customers in Surabaya. This study used quantitative research methods by surveying 250 bridal and make-up business consumers in Surabaya. Then the data obtained was processed using Partial Least Squares. The results of the study prove that service quality, product quality, and fairness of prices have a positive effect on consumer satisfaction and repurchase interest.